Epoxy resin adhesive with high bonding strength and preparation method thereof

By introducing functional groups on the surface of nanocarbon tubes and forming chemical crosslinking with epoxy resin, combining functionalized graphene and hyperbranching coupling agent, the problem of insufficient conductivity and dispersion of epoxy resin adhesives is solved, and high conductivity is achieved and the improvement of high bonding strength, suitable for electronic packaging and electromagnetic shielding.

CN119193073AInactive Publication Date: 2024-12-27湖南君元新材料科技有限公司

Patent Information

Application Number
CN202411678137.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent
Patent Text Reader

Abstract

The invention discloses an epoxy resin adhesive with high bonding strength and a preparation method of the epoxy resin adhesive, belongs to the field of epoxy resin adhesives, and discloses the epoxy resin adhesive with the high bonding strength and the preparation method of the epoxy resin adhesive. Comprising epoxy resin, a modified flexibilizer with a multifunctional cross-linked structure, a functionalized graphene reinforced filler, a hyperbranched polyether type coupling agent, a reactive tackifier, a low-temperature rapid curing agent, a conductive modified carbon nanotube and an anti-aging nano coating agent, due to the introduction of the functionalized modified carbon nanotubes, the epoxy resin adhesive has excellent conductivity, bonding strength, mechanical properties and multifunctional characteristics, the problems of insufficient conductivity, poor dispersity of the carbon nanotubes, insufficient interface bonding force and the like in the traditional technology are solved, and the epoxy resin adhesive becomes an important improvement technology for high-performance bonding materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of epoxy resin adhesives, and more specifically to an epoxy resin adhesive with high bonding strength and a preparation method thereof. Background Art

[0002] Epoxy resins are widely used in structural bonding, electronic packaging and composite materials due to their excellent mechanical properties, chemical resistance and good bonding ability. However, the traditional epoxy resin systems still have the following technical problems that have not been successfully solved in these applications: 1. Insufficient conductivity: Traditional epoxy resin materials are electrical insulators. In applications such as electronic packaging, antistatic and electromagnetic shielding, adhesives are required to have high conductivity. Although conductive fillers (such as silver powder, copper powder, etc.) are often used to improve conductivity, the use of these fillers will significantly increase material costs and easily cause metal ion migration, affecting conductive stability; 2. Poor dispersion of carbon nanotubes: As a nanomaterial with high conductivity and high strength, carbon nanotubes (CNTs) can theoretically significantly improve the conductivity and bonding strength of epoxy resin. However, the hydrophobicity and strong van der Waals force of carbon nanotubes make it easy for them to agglomerate in epoxy resin and difficult to disperse evenly, which results in the failure to fully exert the conductivity and reinforcement effects of carbon nanotubes, limiting their practical application in epoxy resin; 3. Insufficient interfacial bonding: Even in some cases, carbon nanotubes can be dispersed to a certain extent in the epoxy resin matrix, but due to their surface chemical inertness, the interfacial bonding force with the epoxy resin matrix is ​​weak, resulting in poor bonding strength of the carbon nanotube-reinforced composite material after curing, making it difficult to meet the requirements of high-performance structural bonding; Therefore, we propose an epoxy resin adhesive with high bonding strength and a preparation method thereof to solve the above-mentioned problems. Summary of the invention

[0003] 1. Technical issues to be solved In view of the problems existing in the prior art, the purpose of the present invention is to provide an epoxy resin adhesive with high bonding strength and a preparation method thereof. The introduction of functionalized modified carbon nanotubes enables the epoxy resin adhesive to have excellent conductivity, bonding strength, mechanical properties and multifunctional properties, overcoming the problems of traditional technologies such as insufficient conductivity, poor dispersion of carbon nanotubes and insufficient interface adhesion, and becoming an important improvement technology for high-performance adhesive materials.

[0004] 2. Technical solution To solve the above problems, the present invention adopts the following technical solutions.

[0005] An epoxy resin adhesive with high bonding strength comprises a main agent and an auxiliary agent, wherein the main agent comprises the following components in percentage by weight: Epoxy resin: 30-60%; The auxiliary agent comprises the following components by weight percentage: Modified toughening agent with multifunctional cross-linked structure: 5-15%, made by compounding a polymer network modified by nanoparticles and an aromatic polyamide block copolymer; The modified toughening agent with a multifunctional cross-linked structure is mainly prepared by copolymerizing a high-strength and high-flexibility polyamide-polyetheramide network composite polymer chain formed by copolymerizing polyparaphenylene terephthalamide (PPTA) of an aromatic polyamide component with a polyetheramide block and nano-silica (particle size of 20-50 nm) whose surface is modified by γ-glycidyloxypropyltrimethoxysilane and dispersed therein. Physical and chemical cross-linking is achieved between molecules, so that the entire system maintains both high strength and excellent toughness, thereby improving the bonding strength and durability of the adhesive under high stress conditions; Functionalized graphene reinforced filler: 3-12%, graphene modified by carboxyl and hydroxyl groups; Hyperbranched polyether coupling agent: 2-8%, enhances the chemical bonding between epoxy resin and inorganic substrate; Reactive tackifier: 3-10%, the tackifier is a copolymer of amino-terminated modified epoxy resin and maleimide resin; Low temperature fast curing agent: 3-10%, selected from amine composite curing agent, capable of achieving fast curing below 50°C; Conductive modified carbon nanotubes: 1-5%, with charge-capturing functional groups on their surface, which enhance the conductivity and dispersibility of the adhesive layer; The conductive modified carbon nanotubes are carbon nanotubes that have been oxidized by mixed acid treatment of nitric acid and sulfuric acid to form carboxylated carbon nanotubes with polar groups such as carboxyl, hydroxyl, and amino groups on their surfaces. These groups not only enhance the dispersibility of the carboxylated carbon nanotubes in the epoxy resin, but also react with the epoxy groups of the epoxy resin. Anti-aging nano coating agent: 0.5-3%, a complex of nano zinc oxide and nano titanium dioxide, with anti-ultraviolet and antioxidant properties.

[0006] Furthermore, the epoxy resin is a bisphenol F epoxy resin terminated with terminal hydroxyl groups, which can form a multi-point chemical cross-linking structure with the functionalized graphene reinforced filler and the hyperbranched polyether coupling agent, thereby further improving the bonding strength.

[0007] Furthermore, the functionalized graphene reinforced filler is natural graphite, and the graphite is oxidized into graphite oxide by strong acid using the Hummers method, and then single-layer or multi-layer graphene oxide sheets are obtained by ultrasonic or mechanical exfoliation, so that it has a large number of functional groups such as hydroxyl (-OH), carboxyl (-COOH) and epoxy (-O-) distributed on the basal surface and edge of the graphene. These functional groups can significantly improve its compatibility with epoxy resin. The hydroxyl and carboxyl groups can chemically react with the epoxy groups to form covalent bonds, thereby enhancing the interfacial adhesion between the two.

[0008] Furthermore, the hyperbranched polyether coupling agent is a hyperbranched polyether amine that uses polyoxyethylene as a skeleton, generates a hyperbranched structure by stepwise polymerization or ring-opening polymerization, and then introduces terminal amino groups by reaction with polyamine compounds. The terminal amino groups can undergo cross-linking reactions with epoxy groups in epoxy resins, thereby enhancing the curing reaction of epoxy resins. At the same time, the polyether segments in the branched structure can undergo physical adsorption or chemical bonding with hydroxyl groups or oxide layers on the surface of inorganic materials (such as glass or metals) to form strong interfacial bonding.

[0009] Furthermore, the low-temperature fast curing agent is an isocyanate-modified alicyclic amine with a cyclic structure in the molecule. The high activity and low volatility of the alicyclic amine enable it to undergo a cross-linking reaction with the epoxy group below 50°C, thereby achieving rapid curing, and providing good bonding strength, and forming excellent functional characteristics of chemical resistance and mechanical properties after curing.

[0010] Furthermore, the anti-aging nano coating agent can form a nano-scale protective coating on the surface of the adhesive, which has excellent anti-ultraviolet and anti-oxidation capabilities, thereby extending the service life of the adhesive, and is particularly suitable for use outdoors and in harsh environments.

[0011] A method for preparing an epoxy resin adhesive with high bonding strength comprises the following steps: Step 1: adding epoxy resin, functionalized graphene reinforcing filler, modified toughening agent and hyperbranched coupling agent into the barrel of a stirring device according to weight percentage, and then fully mixing at a stirring speed of 1000-2000 rpm for 15-25 minutes; Step 2: Add the reactive tackifier, the conductive modified carbon nanotubes and the anti-aging nano coating agent to the mixture obtained in step 1 according to the weight percentage into the barrel of the stirring device, and continue stirring for 10-15 minutes at a stirring speed of 1000-2000 rpm to make it fully and evenly dispersed; Step 3: Finally, add a low-temperature fast curing agent into the barrel of the stirring device according to the weight percentage, and stir at a low speed of 100-200 rpm to form a uniform adhesive mixture; Step 4: Pour the obtained adhesive mixture out of the barrel of the stirring equipment and then add it into the material box of the vacuum degassing equipment for vacuum degassing treatment. Control the heating mechanism in the material box to heat the adhesive mixture, and control the heating degassing temperature to 40-50°C, the vacuum degree to -0.09 to -0.1 MPa, and the duration to 10-15 minutes to ensure that there are no bubbles in the adhesive.

[0012] Furthermore, the epoxy resin adhesive can be pre-treated by low-temperature heating in a water bath before use, so that its bonding performance is further improved before bonding, the pre-treatment temperature is 40-60° C., and the pre-treatment time is 15-30 minutes.

[0013] 3. Beneficial effects Compared with the prior art, the advantages of the present invention are: (1) This solution introduces charge-capturing functional groups such as carboxyl, hydroxyl, and amino groups on the surface of carbon nanotubes. The modified carbon nanotubes can capture and effectively transfer charges, greatly improving the conductivity of epoxy resin adhesives. This allows the epoxy resin adhesive layer to have good conductivity in applications such as electronic packaging, antistatic, and electromagnetic shielding. Compared with the traditional technical solution using metal conductive fillers, this solution has lower material costs, avoids the problem of metal ion migration, and improves conductivity stability and long-term reliability. (2) In this scheme, the surface of carbon nanotubes is modified by functionalization. The modified carbon nanotubes have polar functional groups on their surface. These functional groups have good hydrophilicity or polymer affinity, so that the carbon nanotubes can be evenly dispersed in the epoxy resin matrix, avoiding the agglomeration of carbon nanotubes in the matrix, thereby ensuring that the carbon nanotubes form a uniform reinforced network structure in the epoxy resin, thereby achieving a synergistic improvement in conductivity and mechanical properties to meet the needs of high-performance applications; (3) In this scheme, the surface functional groups of functionalized carbon nanotubes not only improve their dispersibility in the epoxy resin matrix, but also can undergo chemical cross-linking reaction with the epoxy groups in the epoxy resin to enhance the bonding force between the carbon nanotubes and the matrix interface. In particular, by introducing reactive functional groups such as amino, carboxyl, and hydroxyl groups, the chemical bonding strength between the carbon nanotubes and the epoxy resin matrix is ​​effectively improved, thereby significantly enhancing the overall mechanical properties of the adhesive layer, including tensile strength, shear strength, and fracture toughness. (4) This solution, combined with the use of amine composite curing agents, can achieve rapid curing of epoxy resin in an environment below 50°C. This technology not only improves production efficiency and shortens curing time, but also ensures the formation of high-strength and high-toughness cured products under low temperature conditions, making it suitable for low-temperature bonding and industrial applications requiring rapid curing; (5) In this scheme, while improving the conductivity, the functionalized carbon nanotubes also improve the mechanical properties of the material through uniform dispersion and chemical cross-linking. In particular, after improving the conductivity, it still maintains good fracture toughness, impact resistance and fatigue performance, ensuring the stability and durability of the epoxy resin adhesive under dynamic load. Therefore, the modified adhesive can show excellent comprehensive performance in applications requiring high strength and high toughness, such as mechanical structure bonding and composite materials. Compared with the traditional metal filler scheme, the use of carbon nanotubes greatly reduces the material cost. In addition, the modified carbon nanotubes have good dispersibility and processing properties, making them easy to use in different epoxy resin systems, meeting the needs of different industrial fields for adhesive materials. DETAILED DESCRIPTION

[0014] The technical solutions in the embodiments of the present invention are clearly and completely described below; it is obvious that the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments, and all other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention without making creative work are within the scope of protection of the present invention.

[0015] Example: An epoxy resin adhesive with high bonding strength includes a main agent and an auxiliary agent, wherein the main agent includes the following components in percentage by weight: Epoxy resin: 30-60%; The additives include the following components in percentage by weight: Modified toughening agent with multifunctional cross-linked structure: 5-15%, made by compounding a polymer network modified by nanoparticles and an aromatic polyamide block copolymer; The modified toughening agent with a multifunctional cross-linked structure is mainly prepared by copolymerizing a high-strength and high-flexibility polyamide-polyetheramide network composite polymer chain formed by copolymerizing poly(p-phenylene terephthalamide) (PPTA) of an aromatic polyamide component with a polyetheramide block and nano-silica (particle size of 20-50 nm) whose surface is modified by γ-glycidyloxypropyltrimethoxysilane and dispersed therein. Physical and chemical cross-linking is achieved between the molecules, so that the entire system maintains both high strength and excellent toughness, thereby improving the bonding strength and durability of the adhesive under high stress conditions. Functionalized graphene reinforced filler: 3-12%, graphene modified by carboxyl and hydroxyl groups; Hyperbranched polyether coupling agent: 2-8%, enhances the chemical bonding between epoxy resin and inorganic substrate; Reactive tackifier: 3-10%, the tackifier is a copolymer of amino-terminated modified epoxy resin and maleimide resin; Low temperature fast curing agent: 3-10%, selected from amine composite curing agent, capable of achieving fast curing below 50°C; Conductive modified carbon nanotubes: 1-5%, with charge-capturing functional groups on their surface, which enhance the conductivity and dispersibility of the adhesive layer; Conductive modified carbon nanotubes are carbon nanotubes treated by mixed acid oxidation of nitric acid and sulfuric acid to form carboxylated carbon nanotubes with polar groups such as carboxyl, hydroxyl, and amino groups on their surfaces. These groups not only enhance the dispersibility of the carboxylated carbon nanotubes in the epoxy resin, but also react with the epoxy groups of the epoxy resin. Anti-aging nano coating agent: 0.5-3%, a complex of nano zinc oxide and nano titanium dioxide, with anti-ultraviolet and antioxidant properties.

[0016] A method for preparing an epoxy resin adhesive with high bonding strength comprises the following steps: Step 1: Preparation of modified carbon nanotubes: Commercially available multi-walled carbon nanotubes (MWCNTs) are oxidized by a mixed acid of nitric acid and sulfuric acid to form carbon nanotubes with carboxyl groups (-COOH) on the surface. After ultrasonic dispersion and filtration and washing, carboxylated carbon nanotubes (CNT-COOH) are obtained for subsequent conductivity enhancement of adhesives. Step 2: Mixing and dispersing. After mixing the bisphenol F epoxy resin and the modified toughening agent with a multifunctional cross-linking structure in proportion, use a high-speed stirrer to stir at 1200 rpm for 15 minutes to form a uniform mixture, and then gradually add the carboxylated carbon nanotubes in step 1 to the mixture, continue stirring for 20 minutes, and disperse by ultrasound for 30 minutes to ensure uniform dispersion of the carbon nanotubes in the epoxy resin and prevent carbon nanotubes from agglomerating.

[0017] Step 3: Add coupling agent and other additives, add hyperbranched polyether coupling agent to the above mixture and continue stirring for 10 minutes to allow the coupling agent to react with the epoxy resin and carbon nanotubes at the interface to further enhance the bonding performance, and then add functionalized graphene reinforcing filler, reactive tackifier and anti-aging nano coating agent, and continue stirring for 10 minutes to fully mix them; Step 4: Add curing agent. Add low-temperature fast curing agent to the mixture and stir at low speed for 5 minutes to ensure that the curing agent is evenly distributed in the system. Then place the mixture under vacuum conditions (vacuum degree is -0.08 MPa) and degas for 15 minutes to eliminate bubbles in the adhesive and ensure that a dense bonding layer is formed after curing.

[0018] Step 5: Coating and curing. Coat the prepared epoxy resin adhesive on the surface of the substrate to be bonded (aluminum alloy as the substrate), and heat and cure it at 50°C for 2 hours. In an environment below 50°C, the amine composite curing agent can quickly cure the epoxy resin to form a high-strength bonding layer.

[0019] Step 6: Performance test, bonding strength test: The bonding strength is tested using a tensile shear test device, and the conventional epoxy resin glue and the modified epoxy resin glue prepared in this embodiment are compared and tested. The results show that the shear strength of the modified epoxy resin glue in this embodiment reaches 35 MPa, which is about 40% higher than the shear strength of the conventional epoxy resin glue. Conductivity test: The volume resistivity of the bonding layer was tested by the four-probe method. The volume resistivity of the carbon nanotube-enhanced epoxy resin adhesive in this embodiment was 2.1×10 - ³ Ω·cm, significantly improved conductivity, suitable for conductive bonding or electromagnetic shielding applications; Aging resistance test: UV aging test was carried out on the cured adhesive samples. The test results showed that the epoxy resin adhesive with anti-aging nano-coating agent still maintained more than 85% of its original strength after being exposed to ultraviolet rays for 72 hours, showing excellent anti-ultraviolet aging performance. Step seven: Conclusion. This embodiment successfully prepared an epoxy resin adhesive with high conductivity, high bonding strength and low-temperature fast curing ability by introducing surface carboxyl-grouped carbon nanotubes into the epoxy resin system and combining it with a low-temperature fast curing agent and a toughening agent. Compared with traditional epoxy resin adhesives, this technical solution significantly improves the bonding strength, conductivity and aging resistance, and is suitable for electronic packaging, structural bonding, electromagnetic shielding and other fields.

[0020] The above is only a preferred specific implementation of the present invention; however, the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solution and its improved conception within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An epoxy resin adhesive with high bonding strength, comprising a main agent and an auxiliary agent, characterized in that: The main agent includes the following components by weight percentage: Epoxy resin: 30-60%; The auxiliary agent comprises the following components by weight percentage: Modified toughening agent with multifunctional cross-linked structure: 5-15%, made by compounding a polymer network modified by nanoparticles and an aromatic polyamide block copolymer; The modified toughening agent with a multifunctional cross-linked structure is mainly prepared by copolymerizing a high-strength and high-flexibility polyamide-polyetheramide network composite polymer chain formed by copolymerizing polyparaphenylene terephthalamide (PPTA) of an aromatic polyamide component with a polyetheramide block and nano-silica (particle size of 20-50 nm) whose surface is modified by γ-glycidyloxypropyltrimethoxysilane and dispersed therein. Physical and chemical cross-linking is achieved between molecules, so that the entire system maintains both high strength and excellent toughness, thereby improving the bonding strength and durability of the adhesive under high stress conditions; Functionalized graphene reinforced filler: 3-12%, graphene modified by carboxyl and hydroxyl groups; Hyperbranched polyether coupling agent: 2-8%, enhances the chemical bonding between epoxy resin and inorganic substrate; Reactive tackifier: 3-10%, the tackifier is a copolymer of amino-terminated modified epoxy resin and maleimide resin; Low temperature fast curing agent: 3-10%, selected from amine composite curing agent, capable of achieving fast curing below 50°C; Conductive modified carbon nanotubes: 1-5%, with charge-capturing functional groups on their surface, which enhance the conductivity and dispersibility of the adhesive layer; The conductive modified carbon nanotubes are carbon nanotubes that have been oxidized by mixed acid treatment of nitric acid and sulfuric acid to form carboxylated carbon nanotubes with polar groups such as carboxyl, hydroxyl, and amino groups on their surfaces. These groups not only enhance the dispersibility of the carboxylated carbon nanotubes in the epoxy resin, but also react with the epoxy groups of the epoxy resin. Anti-aging nano coating agent: 0.5-3%, a complex of nano zinc oxide and nano titanium dioxide, with anti-ultraviolet and antioxidant properties.

2. The epoxy resin adhesive with high bonding strength according to claim 1, characterized in that: The epoxy resin is a bisphenol F epoxy resin terminated with terminal hydroxyl groups, and can form a multi-point chemical cross-linking structure with the functionalized graphene reinforced filler and the hyperbranched polyether coupling agent, thereby further improving the bonding strength.

3. The epoxy resin adhesive with high bonding strength according to claim 1, characterized in that: The functionalized graphene reinforcing filler is natural graphite. The graphite is oxidized into graphite oxide by strong acid using the Hummers method, and then single-layer or multi-layer graphene oxide sheets are obtained by ultrasonic or mechanical exfoliation, so that a large number of functional groups such as hydroxyl (-OH), carboxyl (-COOH) and epoxy (-O-) are distributed on the basal surface and edge of the graphene. These functional groups can significantly improve its compatibility with epoxy resin. The hydroxyl and carboxyl groups can chemically react with the epoxy groups to form covalent bonds, thereby enhancing the interfacial adhesion between the two.

4. The epoxy resin adhesive with high bonding strength according to claim 1, characterized in that: The hyperbranched polyether coupling agent is a hyperbranched polyether amine that uses polyoxyethylene as a skeleton, generates a hyperbranched structure by stepwise polymerization or ring-opening polymerization, and then introduces terminal amino groups by reaction with polyamine compounds. The terminal amino groups can undergo cross-linking reaction with epoxy groups in epoxy resins, thereby enhancing the curing reaction of epoxy resins. At the same time, the polyether segments in the branched structure can undergo physical adsorption or chemical bonding with hydroxyl groups or oxide layers on the surface of inorganic materials (such as glass or metals) to form strong interface bonding.

5. The epoxy resin adhesive with high bonding strength according to claim 1, characterized in that: The low-temperature fast curing agent is an isocyanate-modified alicyclic amine with a cyclic structure in the molecule. The high activity and low volatility of the alicyclic amine enable it to undergo a cross-linking reaction with the epoxy group below 50°C, thereby achieving rapid curing and providing good bonding strength, and forming excellent functional characteristics of chemical resistance and mechanical properties after curing.

6. The epoxy resin adhesive with high bonding strength according to claim 1, characterized in that: The anti-aging nano coating agent can form a nano-level protective coating on the surface of the adhesive, and has excellent anti-ultraviolet and anti-oxidation capabilities, thereby extending the service life of the adhesive, and is particularly suitable for use outdoors and in harsh environments.

7. A method for preparing an epoxy resin adhesive with high bonding strength, characterized in that: The following steps are involved: Step 1: adding epoxy resin, functionalized graphene reinforcing filler, modified toughening agent and hyperbranched coupling agent into the barrel of a stirring device according to weight percentage, and then fully mixing at a stirring speed of 1000-2000 rpm for 15-25 minutes; Step 2: Add the reactive tackifier, the conductive modified carbon nanotubes and the anti-aging nano coating agent to the mixture obtained in step 1 according to the weight percentage into the barrel of the stirring device, and continue stirring for 10-15 minutes at a stirring speed of 1000-2000 rpm to make it fully and evenly dispersed; Step 3: Finally, add a low-temperature fast curing agent into the barrel of the stirring device according to the weight percentage, and stir at a low speed of 100-200 rpm to form a uniform adhesive mixture; Step 4: Pour the obtained adhesive mixture out of the barrel of the stirring equipment and then add it into the material box of the vacuum degassing equipment for vacuum degassing treatment. Control the heating mechanism in the material box to heat the adhesive mixture, and control the heating degassing temperature to 40-50°C, the vacuum degree to -0.09 to -0.1 MPa, and the duration to 10-15 minutes to ensure that there are no bubbles in the adhesive.

8. The method for preparing an epoxy resin adhesive with high bonding strength according to claim 7, characterized in that: The epoxy resin adhesive can be pre-treated by low-temperature heating in a water bath before use, so that its bonding performance is further improved before bonding, the pre-treatment temperature is 40-60° C., and the pre-treatment time is 15-30 minutes.

Citation Information

Patent Citations

  • Super-wear-resistant self-lubricating carbon nano polymer material and preparation method thereof

    CN113717496A

  • Graphene reinforced anti-corrosion adhesive tape and preparation method thereof

    CN118909560A

  • Building material composed of fiber-reinforced plastic

    JP2003306856A

  • Novel polyetheramide-imide epoxy resin blends

    US4118535A

Cited By

  • Preparation method and bonding method of bonding glue for infrared detector

    CN119432284A